2017
DOI: 10.1080/16549716.2017.1381462
|View full text |Cite
|
Sign up to set email alerts
|

Paid staff or volunteers – does it make a difference? The impact of staffing on child outcomes for children attending community-based programmes in South Africa and Malawi

Abstract: Background: Globally, and in low and middle income countries (LMIC) specifically, there is a critical shortage of workers. The use of volunteers to support such care delivery systems has been examined, there is scant literature on the impact of volunteers on child outcome in high human immunodeficiency virus (HIV)-affected communities. Objectives: To examine the differential impact of paid versus volunteer workforce in Community Based Organisations (CBOs) providing care to children and families affected by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…While these education‐related outcomes differed between studies, they were generally related to motivation or performance within school, and may be considered to be measures of educational risk. Previous studies have combined various measures of school attendance and performance into an overall measure of educational risk (Tomlinson et al, 2017). One study included both educational and cognitive outcomes (Tomlinson et al, 2017); it was included in both analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While these education‐related outcomes differed between studies, they were generally related to motivation or performance within school, and may be considered to be measures of educational risk. Previous studies have combined various measures of school attendance and performance into an overall measure of educational risk (Tomlinson et al, 2017). One study included both educational and cognitive outcomes (Tomlinson et al, 2017); it was included in both analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have combined various measures of school attendance and performance into an overall measure of educational risk (Tomlinson et al, 2017). One study included both educational and cognitive outcomes (Tomlinson et al, 2017); it was included in both analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, recent work has shown that adequate remuneration is not only essential for staff retention, 56,57 but also plays a role in intervention efficacy. 58 As noted by Gladstone et al, 59 CHWs may feel that they are performing tasks over and above those befitting their pay. Rather than focusing on individual health-workers capacity to deliver a verbatim intervention, the focus should be on assessing whether individual staff members feel confident in their work, and guided by the overall mission, vision, and values of the intervention.…”
Section: Lesson 5-leadership Mattersmentioning
confidence: 98%
“…If projects are to endure and be sustainable, all staff need to have opportunities for growth. Similarly, recent work has shown that adequate remuneration is not only essential for staff retention, but also plays a role in intervention efficacy . As noted by Gladstone et al ., CHWs may feel that they are performing tasks over and above those befitting their pay.…”
Section: Synthesismentioning
confidence: 99%